South African Student Leadership Unrest and Unsettled Constructions: A CIBART Analysis - Pule, N. (South African Journal of Higher Education, 2022)
Student leadership in South Africa is unsettled and characterised by unrest. The perturbing changes in the higher education system, including global shifts and crises, impact South African student leadership psychologically. Consequently, this article seeks to understand the system psychodynamics of South African student leadership. Data was collected during a social dream drawing (SDD) session with student leaders at a South African university before the onset of the Fees Must Fall movement. The SDD session aimed to understand the social construction of student leadership at a South African university and data was analysed through discourse analysis with a psychodynamic interpretation. For this article, a co-reflector was incorporated for secondary analysis after Fees Must Fall to reorganise, reinterpret the data and enhance the initial findings using a conflict, identity, boundaries, authority, role, task (CIBART) model. CIBART findings show that students have a need for a collective and shared vision, and find it unsettling when this need is not satisfied due to the complex environment. Thereby, their psychological safety is threatened, while anxiety is heightened in an environment characterised by transformation and decolonisation agendas. Substantial conflicts impact authority dynamics while, simultaneously, student leadership identity and boundaries are blurry and in crisis. Thus, the compromised clarity of student leadership elevates implications for the confidence that is required for the role and task of student leadership. Consequently, efforts to reduce the anxiety of student leadership ought to be a priority. Psychologists are indicated to play a crucial role in restoring the psychological safety and security of student leaders.